INTEGRATING CHRISTIAN VALUES INTO NURSING ETHICS: MENGINTEGRASIKAN NILAI-NILAI KEKRISTENAN DALAM ETIKA KEPERAWATAN - Aleida Agnes Caroline Tumimomor; Putri Isabel Rembet; Trivena Ister Lumi; Chlaudia Pricilia Maria Rintjap; Lucky Paulus Tumbelaka; Morshe Everly Lumansik; Andro R. Runtu; James Edward Lalira (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This article aims to examine in depth how Christian values ​​can be integrated into nursing ethics in professional practice. In the world of nursing that continues to develop and faces various moral dilemmas, the role of spiritual and religious values ​​is becoming increasingly important, especially values ​​derived from Christian teachings. Values ​​such as love, humility, justice, respect for human dignity, and selfless service are integral parts of Christianity that are in line with ethical principles in nursing. With a qualitative approach through a literature review from various reliable sources, this article identifies a strong relationship between the moral principles of Christianity and the principles of professional nursing ethics. The results of the study indicate that nurses who internalize and apply Christian values ​​in their practice will have higher ethical sensitivity, deep moral reflection skills, and more compassionate and holistic services. These findings underline the importance of faith-based continuing education and development for nursing staff, so that they can provide health services that are not only professional, but also spiritually meaningful